My experience as a student-researcher in a university-level research process: an autoethnographic study - Muralidharan, Ananya, author; Beer, Laura E., advisor; Knight, Andrew J., advisor; Jones, Tiffany, committee member (Colorado State University. Libraries, 2024)
Graduate students' perspectives on being involved in the research process in academia is not a common topic in research literature. Specifically, researchers have not often studied graduate students' roles in faculty-led projects. Despite students having experiences being a part of faculty-led projects, they have not used autoethnography to explore their involvement. As a result, this process may be unknown and intimidating for graduate students. Therefore, the purpose of this study was to describe and understand my experiences as a graduate student-researcher involved in a faculty-led research study. The guiding research questions were as follows: 1) What were my experiences as a graduate student- researcher in a faculty-led research process? 2) How did this experience affect my identity development as a graduate student? I categorized findings into three themes: (a) Graduate Student Identity Development (IDD as a researcher, IDD as a student of color, emotions alongside GSIDD), (b) Research Patterns in Academics (observed patterns in faculty, observed patterns in students & comparing their approach with faculty), and (c) Power Dynamics (observed power dynamics, sensitive conversations). Using an autoethnographic approach, I explored my participation in a faculty-led study to offer insight into how this process affected my graduate student identity development, and how the power dynamics present in student-advisor and student-faculty relationships played a role in this process. These findings provide insight into my experiences being a part of the faculty-led research study and highlight that more student-led research is needed in this space of academia. Discussion about connections between codes and subthemes, connections between the literature and my experiences, reflections on conducting this thesis, and suggestions for students and faculty are included. This thesis contributes to literature by addressing topics like advisor-advisee relationships, power dynamics, and graduate student identity development.
Keywords: culture of white supremacy in academia; identity development; student-advisor dynamics; graduate students; autoethnography; power dynamics